ANALYSIS OF MONETARY AGGREGATE RESPONSE: COMPARATIVE STUDY BETWEEN ISLAMIC AND CONVENTIONAL BANKING SYSTEMS IN INDONESIA - Rina Masruroh; Dadang Suhardi; Munir Nur Komarudin; Wely Hadi Gunawan (Jurnal Akuntansi dan Pajak, 2022)
This research aims to examine which variables most influence the demand for money, and look at the stability of money demand, Islamic and conventional, in response to the shocks of other variables. The analysis method used using Vector Autoregression (VAR), if the data used is stationary at the first difference then the VAR model will be combined with the error correction model into the Vector Error Correction Model (VECM). Impulse response function analysis is also done to see the response of an endogenous variable to the shocks of other variables in the model. The results of this study explained that the shock of the inflation rate responded negatively to the request until the 8th day on sharia demand, while conventionally The shock of the sharia inflation reward rate responded negatively on the 16th day while conventionally there was no response. The shock of the interest rate lift responded negatively on the 11th day on the conventional system while sharia did not respond. While GDP responded positively and stable on day 2 for the Sharia system, while the conventional system responded negatively until the 24th day. . Keywords: inflation rate, inflation reward rate, interest rate, GDP.